Network of Bones : Conjuring Key West and the Florida Keys - Morey, Sean, 1979- (Book collections on Project MUSE., 2019)
Both a far-removed place of refuge for the fringe of society and a high-status vacation destination, the Keys remain a legendary yet fragile place, still threatened by a human-made disaster, the 2010 Deepwater Horizon oil spill. Likewise, Key West, Florida, can be many things to many people, evoking laidback Margaritaville for some and Ernest Hemingway for others. In this mixture of memoir, travel writing, philosophical reflection, natural and cultural history, and meditation on language, Sean Morey wrestles with the varied and often contradictory nature of his hometown. Morey turns a sharp eye inward, teasing out the layers of natural and cultural developments that have shaped the Keys for both millions of years and the past few decades. He asks: What does it take for humans to accept our impact on Earth and, more importantly, what will move humans to take action to reverse adverse impacts? The answer, Morey posits, lies in imaginative thinking--in building connections between locations and individual interests and backgrounds to create a foundation for widespread ecological ethics. In Network of Bones, Morey guides readers through different images of Key West and connects them to global environmental issues, including overfishing, rising sea levels, and polluted oceans. Morey's writing stimulates memory and invites engagement with the world as he shows us how learning about one place--no matter how specific and eccentric that place might be--can teach us about all other places. It's just a matter of imagination. The author's proceeds from the sale of this book will benefit Coastal Conservation Association Florida.